Solar energy controller / Nur Iman Aimi Arzman and Nur Syuhada Zainol - Arzman, Nur Iman Aimi; Zainol, Nur Syuhada (2016)
This project named Solar Energy Controller which the devices that use to prevent battery from damage in solar power system. Other than that, this project used voltage divider rule to measure the voltage levels instead of voltage sensor that expensive so this is one of the reason why it is inexpensive. Moreover, the size of this project is compactable because the battery is placed inside the box which means user friendly and the circuit connection made were connected to Arduino Mega where it helps the circuit to working without fail. Many solar power systems user did not realized about the importance of this controller and most of them faced battery damage problems because lack of knowledge. So, Solar Energy Controller is one step to the solution of their problems and this project was succeeded where the managed to prevent battery from damaged.